Territorial rights - Spark, Muriel (London, United Kingdom : Macmillan Publishing Company, 1979)
Robert wants nothing more than to become a serious art historian. But his hopes for a staid academic life are put on hold when he's driven from London to Venice to escape one lover and seek out another: the enigmatic Bulgarian refugee Lina Pancev. In Venice, Robert encounters a grand carnival of lust, lies, blackmail, cocktail parties, and regicide. As he chases Lina, his heart's desire, the city itself provides a priceless education in love, art, and beauty. Witty yet elegant, Territorial Rights is a celebration of human imperfection and complexity, with as many shifting identities, wardrobe changes, and sumptuous settings as a comic opera.
Keywords: BRITISH